Optimasi Multirespon Gaya Tekan Dan Momen Torsi Pada Penggurdian Material Komposit Glass Fiber Reinforce Polymer (Gfrp) yang Ditumpuk Dengan Material Stainless Steel (SS) Menggunakan Metode Algoritma Genetika - Angga Sateria (Manutech : Jurnal Teknologi Manufaktur, 2017)
Glass fiber reinforced polymer (GFRP)-stainless steel stacks used in the aircraft structural components. The assembly process of this components requires mechanical joining using bolt and nut. The drilling process is commonly used for producing hole to position the bolt correctly. Thrust force and torque are responses that used to evaluate the performance of drilling process. The quality characteristic of these responses are “smaller-is-better.” The aim of this experiment is to identify the combination of process parameters for achieving required multiple performance characteristics in drilling process of GFRP-stainless steel stacks materials. The three important process parameters, i.e., point angle, spindle speed, and feed rate were used as input parameters. Point angle was set at two different levels, whilethe other two were set at three different levels. Hence, a 2 x 3 x 3 full factorial was used as designexperiments. The experiments were replicated two times. The optimization was conducted by using genetic algorithm method. The minimum thrust force and torque could be obtained by using point angle, spindle speed and feed rate of 118o, 2383 rpm, 62 mm/min respectively.